2014
DOI: 10.2478/bvip-2014-0039
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of measuring the concentration of thyroglobulin antibodies in serum of dogs for the assessment of thyroid functioning

Abstract: The aim of the study was to estimate the usefulness of measuring the thyroglobulin antibodies (TgAb s ) concentration in dogs' serum in order to assess thyroid functioning. The study was performed on 383 dogs. The animals were divided into two groups: group A (n = 308) consisted of dogs with hypothyroidism and group B (n = 75) consisted of dogs with euthyreosis. TgAb s was determined in both groups. The reaction to the TgAb s in group A was strongly positive in 32% of dogs, weakly positive in 33% of dogs, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…This agrees with other studies that have reported similar percentages (0-5%) of TgAA in the serum of healthy dogs. 5,14,16,20,23,33,35 The prevalence of TgAA-positive dogs was much higher (28%) in English Setters when compared with the other 6 breeds (0-5%). This finding agrees with a previous report demonstrating that the English Setter breed has the highest prevalence of thyroglobulin antibody (31% of 585 English Setters tested) out of 140,821 serum samples submitted to a commercial diagnostic laboratory for investigation of thyroid disease.…”
mentioning
confidence: 99%
“…This agrees with other studies that have reported similar percentages (0-5%) of TgAA in the serum of healthy dogs. 5,14,16,20,23,33,35 The prevalence of TgAA-positive dogs was much higher (28%) in English Setters when compared with the other 6 breeds (0-5%). This finding agrees with a previous report demonstrating that the English Setter breed has the highest prevalence of thyroglobulin antibody (31% of 585 English Setters tested) out of 140,821 serum samples submitted to a commercial diagnostic laboratory for investigation of thyroid disease.…”
mentioning
confidence: 99%